2022
DOI: 10.1111/medu.14855
|View full text |Cite
|
Sign up to set email alerts
|

Effect of station format on the psychometric properties of Multiple Mini Interviews

Abstract: Background: Given the widespread use of Multiple Mini Interviews (MMIs), their impact on the selection of candidates and the considerable resources invested in preparing and administering them, it is essential to ensure their quality. Given the variety of station formats used and the degree to which that factor resides in the control of training programmes that we know so little about, format's effect on MMI quality is a considerable oversight. This study assessed the effect of two popular station formats (int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 57 publications
2
7
0
Order By: Relevance
“…Moreover, across all three station formats, the correlation with the R score was either absent or very weak, suggesting that all three station formats are assessing non-cognitive attributes. Overall, these results are comparable to the factor analyses recently performed by Renaud et al on the 2010-2017 iterations of the IFMMI, that relied solely on discussion and role-play stations [17]. In this study, all multidimensional models considering station formats had a better fit than the unidimensional models [17].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Moreover, across all three station formats, the correlation with the R score was either absent or very weak, suggesting that all three station formats are assessing non-cognitive attributes. Overall, these results are comparable to the factor analyses recently performed by Renaud et al on the 2010-2017 iterations of the IFMMI, that relied solely on discussion and role-play stations [17]. In this study, all multidimensional models considering station formats had a better fit than the unidimensional models [17].…”
Section: Discussionsupporting
confidence: 89%
“…A fairly consistent finding is that MMI scores are uncorrelated or inversely correlated to GPA or other measures of previous academic performance [11][12][13]. Positive associations were found between MMI scores and OSCE scores in medical school [12,[14][15][16], clerkship rotation evaluations [16][17][18], and in some contexts with exam scores [15]. Two multicenter studies have found correlations between MMI that were developed and implemented by institutions independently [10,19], suggesting some overlap between the constructs assessed in various settings.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations